THE PHENOMENON OF THE CONSUMPTIVE CULTURE OF GENERATION Z IN CILANDAK SUB-DISTRICT IN THE PERSPECTIVE OF BEHAVIORAL ECONOMICS IN THE NEW NORMAL ORDER (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study explores how different societal contexts shape decision-making in consumption behaviors pre-pandemic, post-pandemic, and in revised social norms. Data from Badan Pusat Statistik (2020) demonstrates varied spending during the pandemic: 56% reported increased spending, 17% decreased, and others remained steady. The shift to the new normal amidst COVID-19 in 2022 altered consumer behavior, notably among Generation Z in Cilandak, South Jakarta, known for their digital savvy. The study delves into economic behavior theories, including Thorstein Veblen's idea of Conspicuous Consumption, shedding light on specific purchase rationales. It investigates five economic behavior classifications: Loss Aversion, Endowment Effect, Confirmation Bias, Herd Behavior, and Survivorship Bias. Employing qualitative phenomenological methods with in-depth interviews, it analyzes 13 informants focused on Generation Z in Cilandak. Analysis reveals the Endowment Effect's impact (23.1%) and Confirmation Bias (76.9%) on consumption, highlighting the need for Generation Z's self-awareness and financial literacy. Ultimately, this research offers insights into decision-making and financial skills, guiding Generation Z toward more discerning and responsible consumption habits.
Keywords: Consumption behavior; Generation Z; Behavioral Economics